Penerapan Projek Penguatan Profil Pelajar Pancasila dalam Bidang Konservasi Alam di Sekolah Penggerak SMAN 1 Gerung - Barinta Nur Respasari; Siti Domroh (PT. Anagata Sembagi Education, 2024)
The Pancasila student profile strengthening project is an interdisciplinary project to observe and think about solutions to environmental problems. By utilizing natural resources through the nature conservation program on the independent campus, especially at the driving school in the West Lombok region. The method used in this research is descriptive method with research instruments through interviews, observations, and documentation studies. This research explains and provides an overview of the application of the Pancasila student profile strengthening project in the field of nature conservation at the driving school of SMAN 1 Gerung which produces a work in the form of descriptions of nature, words of wisdom, rhymes, poems by linking several subjects at school. Thus, the importance of implementing an independent curriculum for teachers, students applied in the driving school.